(untitled) (Lectio: Journal of Language and Language Teaching, 2026)
This research aims to identify the various forms of deixis present in the “Roadtrip” album by Ardhito Pramono and uncover their intended meanings in relation to the overall interpretation of the lyrics. Using a descriptive qualitative approach, this study focuses on analysing the lyrics of 10 songs from the album as its primary data. The collected data were categorized into three different types of deixis based on Levinson’s (1983) framework. After classification, the occurrences of deixis were analysed to connect them with their references or contextual meanings within the lyrics. The findings reveal 401 occurrences of person deixis, 52 occurrences of temporal deixis, and 40 occurrences of place deixis. These linguistic elements significantly influence the interpretation of the lyrics by providing clarity and avoiding miscommunication, thereby enriching the listener’s understanding of the songs’ narratives and emotions